Biomarkers of Vitamin D Metabolism and Hip and Vertebral Fracture Risk: The Multi‐Ethnic Study of Atherosclerosis - Simon Hsu; Michael H. Criqui; Charles Ginsberg; Andrew N. Hoofnagle; Joachim H. Ix; Robyn L. McClelland; Erin D. Michos; Steven J. Shea; David Siscovick; Leila R. Zelnick; Bryan R. Kestenbaum; Ian H. deBoer (JBMR Plus, 2022)
ABSTRACT Studies on associations between biomarkers of vitamin D metabolism and fracture risk have focused predominantly on White or elderly populations and may not be generalizable to relatively healthy multiethnic populations. We tested associations of total 25‐hydroxyvitamin D (25[OH]D), the ratio of 24,25‐dihydroxyvitamin D3 to 25‐hydroxyvitamin D3 (vitamin D metabolite ratio, VDMR), parathyroid hormone (PTH), and fibroblast growth factor‐23 (FGF‐23) concentrations measured in serum with risk of hip and vertebral fractures in the Multi‐Ethnic Study of Atherosclerosis (MESA). Serum 25‐hydroxyvitamin D2 and D3 and 24,25‐dihydroxyvitamin D3 were measured by liquid chromatography–tandem mass spectrometry (LC–MS/MS). The study cohort of 6466 participants was without clinically apparent cardiovascular disease and was 39% White, 27% Black, 22% Hispanic, and 12% Chinese. The mean age was 62 years, and 53% were female. There were 128 hip and vertebral fractures over a mean follow‐up of 14.2 years. 25(OH)D, the VDMR, PTH, and FGF‐23 were not significantly associated with fracture risk after adjustment for demographics, diabetes, smoking, systolic blood pressure, body mass index, medication use, albuminuria, and estimated glomerular filtration rate. Principal component analysis did not suggest differences in linear combinations of 25(OH)D, the VDMR, PTH, and FGF‐23 between participants who experienced fractures and those who did not. We did not observe significant interaction between race and ethnicity and any biomarker of vitamin D metabolism on fracture risk. In conclusion, none of the four serum biomarkers of vitamin D metabolism investigated showed a significant association with fracture risk in relatively healthy multiethnic populations. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.